Effects of Using Online Learning and Cooperative Learning Techniques At Senior High School: Comprehension Of EFL - Nurul Hidayati; Emiliana Emiliana; Nurul Aini; Selamet Riadi Jaelani (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
Cooperative learning and online learning are two different approaches to education that have their advantages and disadvantages. The goal of the study to was find out the effects of using online learning and cooperative learning techniques at Senior High school in MUALLIMAT NWDI Pancor comprehension of EFL. The participants of this study were 31 students at MUALLIMAT NWDI PANCOR. To find out the effects of using online learning and cooperative learning faced by the data gained from observation and questioner were analyzed by using thematic analysis. The finding informs that there were three effects of using online learning and three effects of using cooperative learning at Senior High school. In online learning: 1) improve student’s problem-solving ability 2) improve student’s interaction on their learning 3) improve students’ strategies and assessment. In cooperative learning: 1) more comfortable 2) improve communications skills 3) promote social interaction. This study was qualitative research with a case study.